The operational environment and rotational acceleration of asteroid (101955) Bennu from OSIRIS-REx observations - Shelly, F. C.; Howell, E. S.; Fornasier, S.; Golish, D. R.; Scheeres, D. J.; Small, J.; Hanna, K.L. Donaldson; Warren, T.; Millington-Veloza, S.; Allen, B.; McGraw, L.; Johnson, C.L.; et al. (Nature communications, 2019)
During its approach to asteroid (101955) Bennu, NASA’s Origins, Spectral Interpretation, Resource Identiﬁcation, and Security-Regolith Explorer (OSIRIS-REx) spacecraft surveyed Bennu’s immediate environment, photometric properties, and rotation state. Discovery of a dusty environment, a natural satellite, or unexpected asteroid characteristics would have had consequences for the mission’s safety and observation strategy. Here we show that spacecraft observations during this period were highly sensitive to satellites (sub-meter scale) but reveal none, although later navigational images indicate that further investigation is needed. We constrain average dust production in September 2018 from Bennu’s surface to an upper limit of 150 g/s averaged over 34 min. Bennu’s disk-integrated photometric phase function validates measurements from the pre-encounter astronomical campaign. We demonstrate that Bennu’s rotation rate is accelerating continuously at 3.63 ± 0.52 × 10^(–6) degrees/sq. day, likely due to the Yarkovsky–O’Keefe–Radzievskii–Paddack (YORP) effect, with evolutionary implications.